The Effects of Short-Term Exposure to Low Temperatures During the Booting Stage on Starch Synthesis and Yields in Wheat Grain - Zhang, Wenjing; Zhao, Yan; Li, Lingyu; Xu, Xu; Yang, Li; Luo, Zheng; Wang, Beibei; Ma, Shangyu; Fan, Yonghui; Huang, Zhenglai (Frontiers in Plant Science, 2021)
Low temperatures (LT) in spring can have a major impact on the yields of wheat in winter. Wheat varieties with different cold sensitivities (the temperature tolerant Yannong 19 variety and the temperature-sensitive Yangmai 18 variety) were used to study the regulatory mechanisms of responses to short-term LT during the booting stage on the synthesis of wheat grain starch and yields. The effects of short-term LT on the activities of key wheat grain starch synthesis enzymes, starch content and grain dry-matter accumulation were determined by exposing the wheat to simulated LT of from -2 to 2°C. Short-term LT stress caused a decrease in the fullness of the wheat grains along with decreased activities of adenosine diphosphate glucose pyrophosphorylase (AGPase, EC2.7.7.27), soluble starch synthase (SSS, EC2.4.1.21), granule-bound starch synthase (GBSS, EC2.4.1.21) and starch branching enzyme (SBE, EC2.4.1.18) at different spike positions during the filling stage. The rate of grain starch accumulation and starch content decreased with decreasing temperatures. Also, the duration of grain filling increased, the mean and the maximum filling rates were reduced and the quality of the grain dry-matter decreased. The number of grains per spike and the thousand-grain weight of the mature grains also decreased. Our data showed that short-term LT stress at the booting stage caused a decrease in the activities of key starch synthesis enzymes at the grain-filling stage. These changes reduced the accumulation of starch, decreased the filling rate, and lowered the accumulation of grain dry matter to ultimately decrease grain yields.